THE ROLE OF PRINCIPAL'S ACADEMIC SUPERVISION TO TEACHERS AT SMP NEGERI 1 KUALA NAGAN RAYA DISTRICT - Neni Malia (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This research aims to determine the principal's academic supervision of teachers at SMP Negeri 1 Kuala and the obstacles to implementing academic supervision. The approach used is a qualitative approach. Data collection techniques are observation, interviews, documentation and questionnaires. Data were analyzed using the stages of data reduction, data presentation and drawing conclusions. The results of the research show that the implementation of the principal's academic supervision of teachers has been carried out well, the principal has carried out planning by preparing supervision instruments and informing the supervision schedule, implementing supervision using various techniques and principles. Evaluation and follow-up of academic supervision is carried out by discussing the results of supervision with teachers, schools also hold workshops/training with the aim of improving and increasing the quality of teachers in carrying out their duties at school. The implementation of academic supervision experiences obstacles that arise from teachers, namely lack of preparation of learning tools, teachers not mastering the material during the learning process and teachers lacking control over the class, where it appears that students are difficult to control during learning.